K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 10 2018

\(3^2.\left(3x-2\right)=2^3\)

\(9.\left(3x-2\right)=8\)

\(27x-18=8\)

\(27x=26\)

\(x=\frac{26}{27}\)

17 tháng 10 2018

\(3^2.\left(3x-2\right)=2^3\)

\(\Rightarrow\) \(9.\left(3x-2\right)=8\)

\(\Rightarrow\) \(3x-2=\frac{8}{9}\)

\(\Rightarrow\) \(3x=\frac{26}{9}\)

\(\Rightarrow\) \(x=\frac{26}{27}\)

15 tháng 10 2021

\(3x^3+6x^2-3x\Rightarrow ChonD\)

15 tháng 10 2021

D

1: \(=6x^2+2x-15x-5-x^2+6x-9+4x^2+20x+25-27x^3-27x^2-9x-1\)

=-27x^3-18x^2+4x+10

2: =4x^2-1-6x^2-9x+4x+6-x^3+3x^2-3x+1+8x^3+36x^2+54x+27

=7x^3+37x^2+46x+33

5:

\(=25x^2-1-x^3-27-4x^2-16x-16-9x^2+24x-16+\left(2x-5\right)^3\)

\(=8x^3-60x^2+150-125+12x^2-x^3+8x-60\)

=7x^3-48x^2+8x-35

15 tháng 4 2020

   R(x) =           2x2 + 3x - 1

-  M(x) =   -x3 + x2 

                x3 + x2 + 3x - 1

Vậy R(x) - M(x) = x3 + x+ 3x - 1

a: \(=\left(x^2+4\right)\left(x^2-4\right)-\left(x^4-9\right)\)

\(=x^4-16-x^4+9=-7\)

b: \(=27x^3-8-27x^3+6=-2\)

c: \(=\left(3x+5+2-3x\right)^2=7^2=49\)